Pogled članov rehabilitacijskega tima na postavljanje ciljev pri bolnikih po možganski kapi - Bizovičar, Nataša (Zdravniški vestnik, 2019)
Background: Goal setting is a key element in the rehabilitation process of stroke patients. Pa-tient centeredness has not only become an important underlying principle for the delivery of health and rehabilitation services, it has also become an important aspect of the goal-setting process. Current research in the area of stroke rehabilitation suggests that there is a lack of con-sensus concerning best practice for goal-setting. The aim of the study was to determine how rehabilitation team members set rehabilitation goals in patients after stroke, which assessment tools do they use and what obstacles are present during the goal-setting process.Methods: Qualitative semi-structured interviews were conducted with 35 stroke unit rehabili-tation team members at the University Rehabilitation Institute. The interview included questions about clinical experience of goal setting process generally in rehabilitation, the use of assessment tools and problems that arise in setting goals. Results: Most of the team members already used goal setting as a measure of the effectiveness of rehabilitation treatment and perceive goal setting as demanding. Most common mentioned barriers to goal setting were lack of time, and patient characteristics (disease, personality and expectations). Specific improvements were suggested regarding education. Conclusion: This study highlights a number of issues relevant to rehabilitation team members during the goal-setting process in stroke rehabilitation. Rehabilitation process should be patient-centred and goal-directed. In the future, it is important to develop clear guidelines about goal setting in stroke rehabilitation, as well as additional training for healthcare professionals.
Keywords: goal setting; možganska kap; postavljanje ciljev; rehabilitacija; rehabilitacijski tim; rehabilitation; rehabilitation team members; stroke